Responsibility to protect vis-a-vis state sovereignty: the emerging doctrine - Patel, Nirali (Strathmore University, 2018)
The dilemma of how to deal with and respond to humanitarian disasters and large-scale human rights abuses has become more and more the forefront of political and academic debate over the last few decades. The fact is nowadays, due to globalization, there is no longer such a thing as a humanitarian catastrophe occurring 'in a faraway country of which we know little of. As a result, the question of whether or not the international community should still obey the principle of non-intervention, thus allowing the use of sovereignty as an excuse or whether time has come to turn a new leaf to the idea and concept of sovereignty. The concept of 'Responsibility to Protect' is an international norm and has been subject to much debate recently amongst policy makers and academics alike. The international community is acutely aware of the consequences of not having an accepted norm of intervention. While many accept that the UN Security Council's powers to intervene in matters involving horrendous human rights violations are limited, few are willing to recommend an expansion of these powers, predominantly because such a proposition will almost certainly be countered by reference to the inviolability of state sovereignty. State sovereignty has for too long played a starring role in the demise of many attempts to legitimize intervention. The thesis seeks to eliminate this convenience with which the concept of sovereignty is used as an affective legal and political justification for non-intervention by States and regional organizations, and rather turn to look at a new perspective with which the continuing evolution of the responsibility to protect can in fact keep territorial integrity and protect the true sovereignty, as well as provide a reminder to States that they cannot and must not be "innocent and impotent bystanders" of humanitarian disasters and war crimes in foreign countries, furthering that the responsibility to protect, if properly understood, implemented and enforced, provides both conceptual and practical avenues that could help fill the asymmetry between the magnitude of threats to human security and our ability to face them.
Submitted in partial fulfillment of the requirements of the Bachelor of Laws Degree, Strathmore University Law School
Keywords: State sovereignty; Doctrines; Humanitarian disasters; Globalization; International community